PENGARUH UKURAN PERUSAHAAN, KINERJA KEUANGAN, KOMISARIS INDEPENDEN, DAN CAKUPAN ANALIS TERHADAP CORPORATE INTERNET REPORTING Studi Empiris Pada Perusahaan Sektor Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia Tahun 2020 Sampai 2021 - Louis Valentino; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2022)
Increasing internet penetration and increasing internet users, including in Indonesia, are important for companies to disclose information to stakeholders. Considering that the information disclosed by companies varies, it is necessary to understand the effect of firm characteristics on the level of information disclosure via the internet as previous research findings are still inconsistent.This research consists of four independent variables and one dependent variable. In previous studies, the usage of signaling theory was common to explain the disclosure of corporate internet reporting. It is used to distinguish good quality companies from poor quality companies as low-quality companies disclose less information and limit users' access to company information. However, the number of previous publications that uses a ratio-scale index is still limited, especially with developing countries population.This study found significant positive relationship between firm size and analyst coverage towards CIR. An increase in firm size also leads to an increase in agency cost, which needs to be reduced through the act of CIR. Whilst, analyst coverage will motivate managers to do CIR due to an increase of demand. Furthermore, financial performance and independent board do not affect CIR. It is recommended to replace current variables with different ones or add new ones, not limiting social media disclosure only to the hyperlinks to companies' social media, and not limiting disclosure points to 0 or 1 due to the varying level of CIR between companies.